Pertumbuhan ekonomi dengan prespektif regional: PDRB, akumulasi dan alokasi model fisik, manusia dan anggaran - Faradila, Abelia (Maliki Interdisciplinary Journal, 2024)
Progress of a country one of the criteria is stable economic growth or meingngkat in each year. To know how to calculate economic income, it is necessary to have information or knowledge about how to calculate whether a country is classified as a developed country or still a developing country. This article analyzes how the calculation of economic growth and the design used. This article uses descriptive qualitative research methods sourced from several literatures. To determine economic growth, GRDP sums the amount of income or goods and services at current year prices with prices in a given year as the basis. From that sum, GDP estimates whether the economy is growing every year or declining. After knowing the results, it is necessary to have a future-oriented design to prepare a strategy for better economic growth. The purpose of this article is to find out how the system or how GRDP works and what are the things that must be considered related to planning.